Impact of Audience Motivation and Behavior on Concert Experience and Satisfaction among Music Event Attendees (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Music concerts have evolved into significant social and cultural events that offer unique experiences for attendees. However, limited research has examined how audience motivation and behavior influence overall concert satisfaction. This study investigates the relationship between audience motivation, audience behavior, and concert experience satisfaction among music event attendees. A quantitative approach was used, with data collected from 72 respondents via structured questionnaires distributed to concertgoers, extending beyond Tangerang City to capture a diverse range of perspectives. The research employed Structural Equation Modeling (SEM) analysis using WarpPLS software with a Partial Least Squares (PLS) approach to examine the complex relationships between latent variables. The results demonstrate that both audience motivation and behavior significantly influence concert experience and satisfaction (p < 0.05). The model showed strong explanatory power with an Average R-squared (ARS) of 0.654, an Average Path Coefficient (APC) of 0.455, and a Tenenhaus GoF of 0.448, indicating an excellent model fit. Key findings reveal that intrinsic motivations, such as a genuine passion for music and a desire for social connection, drive positive audience behaviors including active participation, emotional engagement, and respectful conduct, which subsequently enhance overall satisfaction and create memorable experiences. The study concludes that concert organizers should develop comprehensive strategies that address both audience motivations and promote positive behaviors to foster safer, more inclusive, and satisfying concert environments. These findings contribute to the academic literature on event management and provide practical recommendations for music industry stakeholders to optimize concert experiences and ensure the sustainability of events. By focusing on the interplay between motivation and behavior, concert organizers can improve attendee satisfaction and enhance the long-term success of music events.